(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In modern technology, Cyber security plays a critical role. Securing data has become one of the most difficult challenges of our time. The first thing that springs to mind when we think of cybersecurity is cybercrime, which is rising. This study aims to determine the Significance of Cyber security to grade 12 HUMSS students at Bestlink College of the Philippines, the basis for securing social accounts. Simple random sampling was used to select a participant who would serve as a respondent. We used qualitative research design, a data collection that uses one or more appropriate methods such as observation and survey. This study on cybersecurity guides us to secure social media accounts to secure their social media security. Despite these precautions, many people are still concerned about cyber security. This study focuses on the issues cybersecurity faces in the modern era, as well as the most recent cybersecurity tactics, ethics, and trends altering the face of cybersecurity. The advent of the internet, various online programs, and ever-evolving social platforms have exposed pupils to online risk.